2018
DOI: 10.1021/acschemneuro.8b00327
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Orthosteric Binding Site of the Human 5-HT3 Receptor Using Photo-cross-linking Antagonists

Abstract: The serotonin-gated 5-HT receptor is a ligand-gated ion channel. Its location at the synapse in the central and peripheral nervous system has rendered it a prime pharmacological target, for example, for antiemetic drugs that bind with high affinity to the neurotransmitter binding site and prevent the opening of the channel. Advances in structural biology techniques have led to a surge of disclosed three-dimensional receptor structures; however, solving ligand-bound high-resolution 5-HT receptor structures has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The structural studies have, to a large degree, refined and elaborated on the molecular understanding of the orthosteric sites initially characterized through mutagenesis and ligand binding approaches [ 15 , 19 , 150 , 151 ]. The three-dimensional structures open up many opportunities to employ additional techniques such as molecular dynamics simulations [ 141 , 142 , 145 , 146 ] in conjunction with photo-crosslinking and mass spectrometry to delve further into the dynamics of ligand receptor interactions [ 152 ]. The transmembrane domains are arranged asymmetrically so transmembrane domain 2 (TM2) faces the pore and contributes most to ion interactions therein ( Figure 2 ).…”
Section: Structural Insights Into 5-ht 3 Receptor Actionmentioning
confidence: 99%
“…The structural studies have, to a large degree, refined and elaborated on the molecular understanding of the orthosteric sites initially characterized through mutagenesis and ligand binding approaches [ 15 , 19 , 150 , 151 ]. The three-dimensional structures open up many opportunities to employ additional techniques such as molecular dynamics simulations [ 141 , 142 , 145 , 146 ] in conjunction with photo-crosslinking and mass spectrometry to delve further into the dynamics of ligand receptor interactions [ 152 ]. The transmembrane domains are arranged asymmetrically so transmembrane domain 2 (TM2) faces the pore and contributes most to ion interactions therein ( Figure 2 ).…”
Section: Structural Insights Into 5-ht 3 Receptor Actionmentioning
confidence: 99%
“…The human C and E subunits also influence the electrical properties in response to 5-HT 3 receptor agonists and antagonists [ 81 , 82 ]. In contrast to humans, rodents only express A and B subunits just forming 5HT 3 A receptor homomers or 5-HT 3 AB receptor heteromers [ 80 , 85 ].…”
Section: Introductionmentioning
confidence: 99%
“…We identified that all subunits are present in some members of Chordata, Mollusca, Platyhelminthes, and Cnidaria. As the A subunit is particularly important in forming the orthosteric binding site [ 85 , 86 ], we investigated how ligand binding components (amino acid residues) in this subunit are altered across the phyla.…”
Section: Introductionmentioning
confidence: 99%
“…These works are enabled by the strategies used in activity-based protein profiling (ABPP), photoaffinity labeling, and advances in mass spectrometry . This strategy has recently been used to great effect to study the activity profiles of NSAIDs, cannabinoid drugs, and methamphetamine, for example. Detailed receptor binding site studies have been enabled by photo-cross-linking the CNS drugs granisetron, propofol, glutamate receptor modulators, and others. DRD2 itself has a long history of use with photoaffinity technology to aid the biochemical characterization of this hard-to-handle membrane-bound protein. , …”
Section: Introductionmentioning
confidence: 99%